Equilibrium and Adsorption Kinetic Study of Metal Ni(II) using Persimmon Tannin Gel - La O. Ahmad; Ulfa H. Syam; Laode A. Kadir; Nohong Nohong; Muh Natsir; Nasriadi Dali; Imran Imran; Tahril Tahril; Thamrin Azis (Universitas Tadulako, 2022)
Heavy metal concentration exceeding the threshold amount is hazardous to the environment, so it needs some treatment. The study aimed to know the capacity and kinetics of adsorption. This study used the adsorption method to remove the heavy metal ion Ni(II) using persimmon tannin gel. Influences of time contact, pH, and ion concentration in the adsorption process were also investigated. Results showed optimum adsorption at 60 minutes of time contact and pH 5. Variation of concentration made the adsorption decrease as metal ion Ni(II) concentration increased. The maximum adsorption capacity was 23.14 mg/g by using pseudo-second-order adsorption kinetic model.